A simple preparation of graphene oxide with a modified Hummer’s method - Anuwongsa, Nattawat; Yawai, Thatsaran; Ananpreechakorn, Watsayod (Indochina Applied Sciences, 2023)
Graphene oxide (GO) has gained a lot of interest in recent years as a key precursor and a derivative of graphene. The GO was retrieved from graphite flakes using a modified Hummer’s approach that differed from the normal Hummer’s method. GO-method 1 using sodium nitrate and GO-method 2 not using sodium nitrate (NaNO3). Used approach is chemical exfoliation, where chemicals are used to intercalate between the graphene layers and expand the interlayer spacing. This expansion weakens the van der Waals forces, making it easier to separate the layers. GO-method 1 and GO-method 2 run on ultrasound and dry. Increasing the ultrasonic process of the procedure reduces the preparation time for graphene oxide compared to the original Hummer’s method. The X-Ray Diffractometer result of GO-method 2 shows the diffraction peaks at 2q at 11.06˚ and 42.24˚ which corresponds to graphene oxide. Raman spectroscopy and UV-visible spectrophotometry were used to investigate the molecular structure and optical properties of graphene oxide, respectively. Field Emission Scanning Electron Microscope of GO to perform elemental mapping on graphene samples and Brunauer Emmet Teller (BET) for surface area determination and pore size distribution results found that GO-method 1 and GO-method 2 corresponds to graphene oxide, which has a macroporous size, and the adsorption response is more respectively.